Analysis of the Effectiveness of the Teaching at the Right Level (TaRL) Approach in Improving Students' Literacy Skills through the 15-Minute Literacy Program at Primary School - Rahmawati, Oka Mania; Oktaviani , Anna Maria; Wijaya, Sastra (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research aims to analyze the effectiveness of the Teaching at the Right Level (TaRL) approach in improving students' literacy skills through a 15-minute literacy program. This approach is based on grouping students according to their ability levels, allowing teaching strategies to be tailored to students' needs. The method used in this study is descriptive with a qualitative approach, where data is collected through observation, interviews, and documentation. Students are grouped based on their reading abilities: beginner, letters, words, paragraphs, and stories. The instruments used in this study are initial diagnostic and developmental tests conducted orally at the beginning and during the research process. These tests measure the overall development of students' reading skills over time. Data analysis is conducted to evaluate students' engagement and their responses to short but intensive literacy activities. The results indicate a significant improvement in students' literacy skills at all reading ability levels, both in comprehension and reading fluency. This improvement suggests that the TaRL approach can effectively enhance elementary school literacy skills. This research is expected to significantly contribute to developing more effective literacy strategies in elementary schools to optimize short yet effective learning time.